2020
DOI: 10.1016/j.aninu.2020.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Effects of stocking density on growth performance, blood parameters and immunity of growing pigs

Abstract: This study was conducted to evaluate the effects of different stocking densities on growth performance, blood parameters, intestinal morphology and intestinal immunity of growing pigs. A total of 288 male pigs (44.35 ± 0.50 kg) were randomly assigned to groups with stocking densities of 2.46, 1.23 and 0.82 m 2 /pig for a month. The results showed that there was no significant difference on growth performance among groups. Pigs in the stocking density of 0.82 m 2 /p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 29 publications
(11 reference statements)
0
4
0
Order By: Relevance
“…Backfat thickness is an important indicator of performance and meat quality. Excessive backfat often has a negative impact on the reproductive performance, immunity, and meat quality of pigs [24,25]. Reducing backfat is key to improving the lean meat percentage, relevant studies have found that mulberry leaves can inhibit the deposition of backfat by promoting the secretion of leptin and the expression of the lipolysis gene HSL in the backfat tissue of pigs and inhibiting the expression of the fatty acid synthesis gene FASN, which is consistent with our results [16].…”
Section: Discussionsupporting
confidence: 90%
“…Backfat thickness is an important indicator of performance and meat quality. Excessive backfat often has a negative impact on the reproductive performance, immunity, and meat quality of pigs [24,25]. Reducing backfat is key to improving the lean meat percentage, relevant studies have found that mulberry leaves can inhibit the deposition of backfat by promoting the secretion of leptin and the expression of the lipolysis gene HSL in the backfat tissue of pigs and inhibiting the expression of the fatty acid synthesis gene FASN, which is consistent with our results [16].…”
Section: Discussionsupporting
confidence: 90%
“…Commercial farming uses 0.7-1 m 2 of space per pig, depending on the country [68][69][70]. It is conceivable that under dense commercial farming condition direct transmission events could be favoured [71,72]. It is also possible that direct transmission is influenced by the viral strain.…”
Section: Discussionmentioning
confidence: 99%
“…The TP level in blood serves as a key indicator of hepatic protein metabolic status in response to dietary supplementation. ALB, the most abundant blood protein, acts as an essential binding transporter for various metabolites, while also providing a constant supply of endogenous AAs [ 36 ]. Our current study detected a significant increase in serum TP and ALB levels as a result of dietary supplementation with magnolol.…”
Section: Discussionmentioning
confidence: 99%